Hubungan Umur Dan Pendidikan Dengan Persepsi Konsumen Mengenai Buah Impor Di Kota Surakarta - Kartika, Fiqi Dwi, Dr. Mutalazimah, SKM, M.Kes, Rusdin Rauf, STP., MP (2016)
Perception is a vision of how people see things. Education and age affect consumers' perceptions of a product that is consumed. A quality product will encourage the perception of consumers to choose and to make a decision based on the information received by consumers. Consumers have different criteria in choosing fruits that will be purchased and consumed so that consumers will choose fruit quality as well as better quality and cheaper prices. In general, the attributes of imported fruit raises appeal to consumers so that consumers tend to buy imported fruit quality and better quality and in accordance with their needs. Quantitative research with cross-sectional approach was conducted. The number of respondents as much as 46 people, were obtained by consecutive random sampling technique. Age and education data were obtained through interviews, while consumer perception of the data obtained using quersioner with number of 22 statements. Rank spearman was used in statistical analysis. More of adults consumers gave the highest perception, was 28,6 % bigger than teenager and elderly, were 20,0 % and 0 % respectively. Consumers with secondary education revealed the perception better than basic and higher educations, were 30,0 %, 0 % and 20,8 % respectively.There was no correlation between age and the perception of consumers regarding the fruit imports in Surakarta evidenced by the value of p > 0.05. There was a correlation between education and consumer perception regarding fruit imports in Surakarta evidenced by the value of p <0.05.